Competitive federalism, government's dual role, and the power to tax - Viktor J. Vanberg (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2015)
Theories of competitive federalism generally focus on exit as the principal mechanism for making governments responsive to the interests of those who are subject to their powers. This paper draws attention to the necessity to specify more clearly the meaning of 'exit' in light of the fact that democratic governments act in two distinguishable roles, namely as what I propose to call 'territorial enterprises' and 'clubs enterprises'. As territorial enterprises, governments define and enforce the rules and conditions under which private law subjects, citizens and non-citizens alike, may pursue their private purposes within the territory of the respective jurisdiction. As club enterprises, governments define and enforce the rules and conditions of membership in the respective political community. Accordingly, individuals are subject to government's power in two capacities. As private law subjects they can choose, like customers, among competing territorial enterprises according to their respective relative attractiveness, separately for the various purposes they pursue. As citizens, they share, as members of a polity, in the inclusive bundle of benefits and costs that come with the membership status. The focus of this paper is on the implications of the fact that 'exit' means something different when one looks at citizens as customers of territorial enterprises (exit = leaving the territory) as opposed to their role as citizens-members (exit = giving up one's membership-status/citizenship).
Keywords: 330